A concise pore structure model for predicting the effective ion diffusion coefficients of cementitious materials. (30th December 2020) - Yang, Jinbo; Zhang, Peng
Highlights: A novel and concise pore structure model (ACTPore model) is proposed. The relationship between porosity and tortuosity is expounded accordingly. Prediction equations of the effective ion diffusion coefficients are derived. Abstract: Ion diffusion property prediction of cementitious materials by modeling pore structure is a hotspot and challenge for cement and concrete research. In a recent paper, Yio et al. examined the 3D structure of capillary pores (>0.24 μm) within 100 3 μm 3 blended cement paste for the first time using laser scanning confocal microscopy (LSCM). The main advantage of LSCM is the ability to characterize the 3D structure of interconnected pores and then to improve the possibility of establishing more effective pore structure models. This contribution proposes a novel and concise pore structure model named accessible cylindrical tortuous pore model (ACTPore model) for describing the physical connections among accessible porosity, mean pore diameter, tortuosity and pore specific surface area. The ACTPore model is proved to be rational and verified by LSCM experimental results.